Highly Substituted Benzophenone Aldehydes and Eremophilane Derivatives from the Deep-Sea Derived Fungus Phomopsis lithocarpus FS508 - Jian-Lin Xu; Hong-Xin Liu; Yu-Chan Chen; Hai-Bo Tan; Heng Guo; Li-Qiong Xu; Sai-Ni Li; Zi-Lei Huang; Hao-Hua Li; Xiao-Xia Gao; Wei-Min Zhang (Marine Drugs, 2018)
Five new benzophenone derivatives named tenellones D–H (1–5), sharing a rare naturally occurring aldehyde functionality in this family, and a new eremophilane derivative named lithocarin A (7), together with two known compounds (6 and 8), were isolated from the deep marine sediment-derived fungus Phomopsis lithocarpus FS508. All of the structures for these new compounds were fully characterized and established on the basis of extensive spectroscopic interpretation and X-ray crystallographic analysis. Compound 5 exhibited cytotoxic activity against HepG-2 and A549 cell lines with IC50 values of 16.0 and 17.6 μM, respectively.